Heat in a Cold Climate: Household Energy Choices in the Scandinavian North, 1890–1970 - Warde, Paul; Lindmark, Magnus (Journal of Northern Studies, 2020)
This article examines the timing, scale and cause of transitions between different kinds of household energy use and especially heating in northern Sweden, with a focus on Norrbotten, between the late nineteenth century and 1970. It examines the related but separate histories of the adoption of new heating technologies, such as stoves and boilers, and the choice of fuels, such as firewood, coke, oil, and electricity, providing new data on the scale of consumption and timing of transition. The article demonstrates the important linkage between domestic fuel choice and labour markets, whether labour in farm and forest affecting stove use in the nineteenth century, or increased female labour participation outside the home and rising wages in the twentieth. The article goes beyond discussions of price and technology to consider the wider contexts of domestic use not only in terms of home life, but also industrial development and labour markets in northern Sweden.